Moduli of surfaces with an anti-canonical cycle. (9th October 2014) - Gross, Mark; Hacking, Paul; Keel, Sean
Abstract: We prove a global Torelli theorem for pairs $(Y, D)$ where $Y$ is a smooth projective rational surface and $D\in |-K_{Y}|$ is a cycle of rational curves, as conjectured by Friedman in 1984. In addition, we construct natural universal families for such pairs.